Microencapsulation Betacyanin Extract from Red Dragon Fruit Peel: Study of Coating Ratio and Concentration: Mikroenkapsulasi Ekstrak Betasianin Kulit Buah Naga Merah: Kajian Rasio dan Konsentrasi Penyalut - Yuwono, Sudarminto Setyo; Khusnia, Nastasya; Waziiroh, Elok (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Red dragon fruit peel has a fairly high content of betacyanin pigment, so it has the potential as a natural food color. However, its stability is influenced by various factors. To maintain its stability, microencapsulation technology can be used with the microwave-assisted foam-mat drying method. Microencapsulation can protect active compounds by forming microcapsules. In this technology, coating materials can affect the characteristics of microcapsules. This study aims to evaluate the interaction between the ratio and concentration of maltodextrin and gum arabic as coating material on the physicochemical properties of betacyanin extract microcapsules and determine the best treatment for microcapsules. This study uses a Randomized Factorial Block Design with two factors, ratio of maltodextrin and gum arabic (2:1, 3:1, 4:1), and concentration of coating materials (10% w/v and 15% w/v). The best treatment was obtained from a coating ratio of 3:1 and a concentration of 15% w/v. The microcapsules have better physicochemical characteristics than microcapsules without coating on solubility, yield, moisture content, and light stability of betacyanin parameters. Abstrak Kulit buah naga memiliki kandungan pigmen betasianin yang cukup tinggi sehingga memiliki potensi sebagai pewarna alami. Namun, kestabilannya dipengaruhi berbagai faktor seperti suhu dan cahaya. Untuk dapat mempertahankan stabilitasnya, dapat digunakan teknologi mikroenkapsulasi dengan metode pengeringan buih microwave. Mikroenkapsulasi dapat melindungi senyawa aktif dengan pembentukan mikrokapsul. Pada mikroenkapsulasi, bahan penyalut dapat mempengaruhi karakteristik mikrokapsul. Penelitian ini bertujuan untuk mengevaluasi interaksi faktor rasio dan konsentrasi penyalut maltodekstrin dan gum arab terhadap sifat fisikokimia mikrokapsul ekstrak betasianin, serta menentukan mikrokapsul perlakuan terbaik. Penelitian ini menggunakan Rancangan Acak Kelompok Faktorial dengan dua faktor, rasio penyalut maltodekstrin dan gum arab (2:1, 3:1, 4:1) serta konsentrasi kombinasi penyalut (10 b/v dan 15 b/v). Perlakuan terbaik didapatkan dari rasio penyalut maltodekstrin dan gum arab 3:1 dengan konsentrasi 15 b/v. Mikrokapsul tersebut memiliki karakteristik fisikokimia yang lebih baik dibandingkan mikrokapsul tanpa perlakuan penyalut pada parameter kelarutan, rendemen, kadar air, dan stabilitas cahaya mikrokapsul.